Pengaruh Pemberian Kotoran Walet terhadap pH, KTK, C-Organik, N-Mineral dan P-Tersedia pada Tanah Ultisol - Maratun Sholikhah; Afiah Hayati; Akhmad Rizalli Saidy (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
This study aims to determine the effect of swallow droppings and its best treatment on pH, CEC, organic-C, mineral-N, and available-P in Ultisols. The research method used was a one-factor Completely Randomized Design (CRD) with an incubation period of two weeks, with five treatments of 0, 2.5, 3.0, and 3.5 t ha-1 swallow droppings. Each treatment repeated four times to make 20 experimental units. Parameters observed were soil pH (H2O), CEC, organic-C, mineral-N, and available-P. The results showed that the application of swallow droppings affected pH, CEC, organic-C, mineral-N, and available-P in Ultisols. Swallow droppings of 3.5 t ha-1 significantly affected mineral-N (N-NH4+ and N-NO3-) and other parameters such as CEC, available-P, pH, and organic-C.